1999
DOI: 10.1007/s007840050101
|View full text |Cite
|
Sign up to set email alerts
|

Elution parameters and HPLC-detection of single components from resin composite

Abstract: The toxic effects of mercury derived from amalgam fillings have been a focus of controversy in Germany during the last 25 years. As alternatives to amalgam, composites are used widely to restore anterior and posterior permanent teeth. This study quantifies the amount of TEGDMA and methacrylic acid that can be derived from a polymerized commercial hybrid composite material. Different specimens were made with different curing methods with and without an oxygen inhibition layer. To simulate the removal of composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 18 publications
0
46
0
4
Order By: Relevance
“…However, for the in vivo situation, in saliva and other body media, there are always enzymes present causing biodegradation of composite resin materials [29]. The use of THF as a solvent to measure the total quantity of residual monomers can be considered the method of choice even though it is a very powerful solvent and can cause damage within the polymer itself [30]. Post-curing considerably reduced the total quantity of residual monomer (both TEGDMA and Bis-GMA) of the specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the in vivo situation, in saliva and other body media, there are always enzymes present causing biodegradation of composite resin materials [29]. The use of THF as a solvent to measure the total quantity of residual monomers can be considered the method of choice even though it is a very powerful solvent and can cause damage within the polymer itself [30]. Post-curing considerably reduced the total quantity of residual monomer (both TEGDMA and Bis-GMA) of the specimens.…”
Section: Discussionmentioning
confidence: 99%
“…This then resulted in weak biofilm attachment that eventually caused the biofilm to detach easily from ES-DP. Another possible factor influencing bacterial adherence to resin composite surfaces was the amount of unpolymerized monomers in cured composites [41][42][43][44] . However, results from ATR-FTIR analysis in this study indicated that slight amounts of residual monomers were detected on the surface of both ES and GR composites.…”
Section: Discussionmentioning
confidence: 99%
“…The use of high performance liquid chromatography (HPLC) in the current study allowed a quantitative analysis of the lixiviation of monomers (µg/mL), resulting in greater accuracy and reliability of the obtained data. However, other studies (Inoue and Hayashi, 1982;Pearson and Longman, 1989;Tanaka et al, 1991;Ferracane, 1994;Spahl et al, 1998;Pelka et al, 1999) reported the amount of leachable components of dental composites as a percentage of the initial weight of the specimen. The leaching curves of the monomers in this study revealed that most of the monomers were lixiviated within the first seven days.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller molecules are expected to leach more and faster than larger molecules (Thompson et al, 1982;Spahl et al, 1998;Pelka et al, 1999;Örtengren et al, 2001). This was observed in the present study by the higher concentration of TEGDMA in all tested composites, when compared to Bis-GMA, which was in agreement with other studies (Tanaka et al, 1991;Spahl et al, 1998;Pelka et al, 1999;Örtengren et al, 2001). The composites Tetric Ceram and Filtek Z250 exhibited high elution of UDMA.…”
Section: Discussionmentioning
confidence: 99%